Community Members’ Perceptions of the CSI Effect - Hayes, Rebecca M. (American journal of criminal justice, 2013)
The CSI Effect is the notion that crime show viewing influences jurors to have unrealistic expectations of forensic evidence, which then affects their trial decisions. Analyses of popular media shows that the media portrays the effect as a real problem, and research surveying the legal community indicates that they believe the CSI Effect exists and may change their investigation and trial strategies accordingly. The present study expanded on this research by surveying community members regarding their perceptions of the CSI Effect. Community members reported their general television and crime show viewing behaviors, and we examined this in relation to their knowledge construction of the CSI Effect. Findings indicate that overall, the majority of community members did not have knowledge of the CSI effect, but those who did perceive it as an unrealistic expectation of evidence. When provided with a definition of the CSI Effect, people generally believed it exists. Additionally, crime show viewing and participant’s race influenced people’s perceptions of the CSI effect. Limitations of this study and directions for future research are also discussed.